Prevalence and molecular determinants of carbapenemase-producing Klebsiella pneumoniae isolated from Jazan, Saudi Arabia - Thamer Brek; Ahmed K Alghamdi; Turki S Abujamel; Muhammad Yasir; Elaf M Alattas; Maryam S Hazazi; Ibrahim A Al-Zahrani (Journal of Infection in Developing Countries)
Introduction: The World Health Organization (WHO) designated Carbapenem-resistant Enterobacterales (CRE), formerly Enterobacteriaceae, among the global priority list of antibiotic-resistant bacteria. The rate of CRE in Arabian countries, including Saudi Arabia has increased. Here, we report the prevalence of carbapenemase-producing Klebsiella pneumoniae (CPKP) in the Jazan region, a southern coastal province of Saudi Arabia.